Animal models of sports‐related head injury: bridging the gap between pre‐clinical research and clinical reality. (19th March 2014) - Angoa‐Pérez, Mariana; Kane, Michael J.; Briggs, Denise I.; Herrera‐Mundo, Nieves; Viano, David C.; Kuhn, Donald M.
Abstract Sports‐related head impact and injury has become a very highly contentious public health and medico‐legal issue. Near‐daily news accounts describe the travails of concussed athletes as they struggle with depression, sleep disorders, mood swings, and cognitive problems. Some of these individuals have developed chronic traumatic encephalopathy, a progressive and debilitating neurodegenerative disorder. Animal models have always been an integral part of the study of traumatic brain injury in humans but, historically, they have concentrated on acute, severe brain injuries. This review will describe a small number of new and emerging animal models of sports‐related head injury that have the potential to increase our understanding of how multiple mild head impacts, starting in adolescence, can have serious psychiatric, cognitive and histopathological outcomes much later in life. <boxed-text content-type="graphic" id="jnc12690-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Sports‐related head injury (SRHI) has emerged as a significant public health issue as athletes can develop psychiatric and neurodegenerative disorders later in life. Animal models have always been an integral part of the study of human TBI but few existing methods are valid for studying SRHI. In this review, we propose criteria for effective animal models of SRHI. Movement of the head upon impact is judged to be of primary importance in leading to concussion and persistent CNS dysfunction.